The Effect of Using Peanut Ball on The Duration of First Stage of Labour: A Systematic Review - Intan Navelia, Zesika; Hanifa, Fatya Nurul; Rusliani, Dian Monalisa; Dewi, Novita Puspita; Heldayasari, Febry (Universitas Islam Jember, 2024)
One of the recommendations made by the World Health Organization (WHO) to prevent protracted labor is to move and change positions frequently during labor. In most private hospitals, however, labor induction, continuous fetal monitoring in a supine position, and immobilization of the woman during labor are normal procedures.The peanut ball is useful tool for addressing these issues and putting WHO recommendations into practice. It allows for frequent positioning changes without interfering with labor procedures. This study aimed to determine effectiveness of peanut ball on the duration of first stage of labour. A systematic literature review. A comprehensive electronic search was carried out with time limit from April 2019 until April 2024. Collected data were analysed by identifying, assessing, and interpreting all findings on a research topic, to answer research questions that have been determined previously. Results: The analysis on twelve clinical trials showed that the use of peanut ball has statistically significant reduce length of the first stage. Suggestion: Further clinical trials with stronger evidence should be carried out to assess the effectiveness of peanut ball on length of first stage of labour.